Listening comprehension strategies used by EFL postgraduate students / Wang Song - Wang, Song (2016)
Malaysian EFL postgraduate students are facing difficulties in listening to lectures in English. Listening comprehension strategies (cognitive, metacognitive and socio-affective) play a crucial role in academic listening. The current study which employs questionnaire survey and follow-up interviews aims to investigate the use of listening comprehension strategies of first-year EFL master‟s degree students of the higher and lower proficiency groups, in order to shed some light on effective acquisition in L2 listening. A total number of 98 EFL postgraduate students responded to a demographic information questionnaire and a listening comprehension questionnaire with a likert-scale. Based on their TOEFL/IELTS listening scores, they are classified into beginning, intermediate and advanced groups. For the purpose of study, only beginning and advanced groups with 68 respondents are selected. Meanwhile, follow-up interviews based on the survey data are conducted individually with 10 selected subjects including five (5) higher proficiency and five (5) lower proficiency students. The survey results show that the higher proficiency group uses the three listening comprehension strategies more frequently than the lower proficiency group. The higher proficiency group uses different varieties of metacognitive strategies and socio-affective strategies more frequently than the lower proficiency group. The interview data are transcribed and analyzed through thematic analysis. The study reveals that fast speed and accent varieties are the most common difficulties for both groups; however, the lower proficiency group added another factor, i.e. vocabulary. Key words: Second language acquisition, listening comprehension strategy, academic listening